Penguatan Dukungan Psikososial Pascabencana Tanah Bergerak melalui Psikoedukasi Berbasis Kekuatan Karakter pada Warga Desa Padasari, Kabupaten Tegal (Lembaga Pengembangan Kinerja Dosen, 2026)
The landslide that occurred in Padasari Village, Jatinegara Subdistrict, Tegal Regency not only caused physical damage but also impacted the psychological well-being of the community. The limited availability of post-disaster psychosocial support services underscores the need for community-based interventions capable of enhancing the community’s adaptive capacity. This community service activity aims to provide psychoeducational training based on character strengths as an effort to strengthen the psychological resilience of disaster-affected communities. The method used is a participatory approach that involves residents as active participants throughout the entire activity process. The program implementation included a preparation phase, followed by the delivery of character strengths-based psychoeducation through presentations, group discussions, exercises to identify character strengths, reflection on experiences, and follow-up discussions on applying character strengths in daily life. The activity was evaluated through question-and-answer sessions, reflective discussions, and observation of participant engagement, using the following indicators: the ability to identify at least three character strengths and active participation in group discussions.